Quality of life in patients with comorbid current rheumatoid arthritis and arterial hypertension - Pekhenko, Valentina; Alifer, Olha (Psychosomatic Medicine and General Practice, 2017)
Background. Much attention is paid to comorbid states, which have a mutually burdensome, provoke exacerbations, impede the completion of full remission, and lead to the development of complications. Such pathology has a particular impact on the functional capabilities of the body, it leads to a patient's lifestyle modification and triggers the problem of social adaptation and deterioration of the quality of life (QOL). Methods. The study included 89 patients with rheumatoid arthritis and arterial hypertension, which were divided into three groups, and 20 practically healthy individuals. The comparative estimation of QOL parameters was performed using the questionnaire SF-36. Results. In all patients with rheumatoid arthritis and hypertension at baseline was noted a reduction in SF-36 scores compared to healthy individuals. The study found that patients' QOL depends on the treatment type and its overall effectiveness. Conclusion. QOL assessment in patients with RA and hypertension allows retrieving additional information about the illness, which can increase treatment effectiveness. The decrease in QOL psychological component may indicate a need for the addition of psychological interventions in treatment plans for these patients.